Hypothyroidism Complicating Nephropathy in a Diabetes Patient - Jayaprakash Sahoo; Ilangovan Veerappan; Anila Abraham; Somasundaram Hariharan (Case Reports in Endocrinology)
We describe a patient with type 2 diabetes mellitus and autoimmune hypothyroidism who presented with elevated serum creatinine possibly due to subclinical rhabdomyolysis induced by hypolipidemic drug therapy in the background of diabetic nephropathy. Both hypothyroidism and rhabdomyolysis were asymptomatic in this case as evidenced by lack of classical clinical features of hypothyroidism despite elevated serum TSH and absent pigment cast in renal biopsy. The combination of diabetes mellitus and hypothyroidism is common in the general population and should not be forgotten in patients with diabetes and kidney disease.